Synthesis of Bis-Cycloborate Olefin and Butatriene Derivatives through the Reduction of Alkynyl-Bridged Diboryl Compounds - Zhao, Jinyu; Ru, Chenglong; Bai, Yunfei; Wang, Xingyong; Chen, Wenhao; Wang, Xi; Pan, Xiaobo; Wu, Jincai (Inorganic chemistry, 2018)
A series of bis-cycloborate olefin and butatriene derivatives were synthesized from alkynyl-bridged diboryl compounds using a simple reduction strategy. In the reduction route of 1,2-bis[2-(dimesitylboranyl)phenyl]ethyne (1), bis-cycloborate olefin (4) to diborate-bridged stilbene (5) can be obtained selectively by varying the reaction temperature. In addition, a thermal isomerization from 4 to 5 was found as a result of the rearrangement of double bonds. The generality of this reaction was further verified in similar reduction reactions. In the direduction of 1,2-bis[8-(dimesitylboranyl)naphthalen-1-yl]ethyne (2), the bis-cycloborate olefin (6) was isolated in high yield and demonstrated no thermal isomerization. In the two-electron reduction of 1,8-bis{[2-(dimesitylboranyl)phenyl]ethynyl}naphthalene (3), the bis-cycloborate butatriene (7) was obtained unexpectedly because of the departure of the naphthyl group. When using Na as the reductant and diethyl ether as the solvent, 1,2-bis[(Z)-2-(dimesitylboranyl)benzylidene]-1,2-dihydroacenaphthylene (8) was isolated after adding 1 or 2 drops of H2O to the reduction reaction filtrates. Meanwhile, the related mechanisms for radical cyclization, thermal isomerization, and formation of bis-cycloborate butatriene were also discussed.